Knowledge, Awareness & Practice (KAP) for COVID-19 in the Pakistani Nation - Tahira Riaz, Sadaf Shafique, Elishba Maryam, Huma Shehzadi, Areej Riaz, Sana Riaz, Muhammad Zulqurnain (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The study aimed to examine COVID-19 knowledge among the general public in Pakistan, to review their attitudes and views regarding the fast epidemic. Study Design: Descriptive cross-sectional study. Duration of Study: June-July 2020. Methodology: A total of 679 respondents included. The questionnaires comprised of the following basic themes: basic demography, general & basic clinical/medical knowledge, attitudes, awareness, perceptions as well as a sense of prevention regarding COVID-19. Results: The majority (75.5%) of the respondents were from Punjab province. Around half (54.5%) of the respondents had heard about the COVID-19 infection through different social media. The majority were 28.4% medical students. The majority of the respondents (80-95%) selected correct answers from the given choices for the questions related to some clinical knowledge. More than half of people (59-64%) think positively that COVID-19 will successfully be controlled and Pakistan will be successful in winning this battle of the pandemic. 61% were afraid of COVID-19 as it is highly contagious disease (37.7%). Around 60% always covered their noses and mouths while sneezing and coughing. Conclusion: The people must have a thorough understanding of COVID-19 to successfully execute COVID-19 prevention strategies. Although we found enough knowledge, favorable perspectives, and readiness to follow SOPs, we believe that additional preventative and cautious attitudes, as well as awareness, are needed.